Is Participation in Social Organizations an Alternative to Improve Household Economic Welfare in Chile? - Salazar, Cesar (Estudios de Economía, 2016)
This research aims to find the determinants of participation on social organizationsin Chile through a social capital approach, as well as to evaluate the existenceof a positive effect between participation and household welfare. In the caseof economic and local organizations several regressions for participation andincome were run. Due to the existence of endogenity of income in participationequation, it was estimated a simultaneous model for recreational organizations.The proposed model includes Two Stage Probit Least Squares estimates suitableto correct for simultaneity bias when one of the variables is continuous and theother is dichotomous. Econometric results point out that age, schooling, houseownership, place of residence and individual perception of both social intercourseand safety in their neighborhoods have a meaningful effect on participation.The study also reported on the positive effect between participation in economicorganizations and household welfare.